Reflections about the Role of Rural Colombian Women in the Work - Meneses Medina, Paula Andrea (Revista Punto Género, 2023)
This article aims to reflect on the role of rural Colombian women in labor, based on gender relations perceived in the activities carried out by women and men in a village in the Cauca Department. It also relies on theoretical-conceptual reflections related to popular education, gender, gender stereotypes, the sexual division of labor, and care work from the perspective of intersectionality. The exercise concludes with three reflections aimed at proposing public policies. Firstly, there is a need to incorporate intersectional analysis in Colombian rural contexts. Secondly, the importance of proposing a popular education that considers aspects such as situated knowledge and includes a gender perspective. Lastly, the presence of gender stereotypes leads rural women to concentrate on care work.